Development of Learning Media Using Smart Apps Creator on ”Introducing Oneself and Others” - Silphia Rizki; Pahmi Pahmi; Prih Febtiningsih (ELT-Lectura, 2022)
Improving the quality of education will contribute to increasing the level of the quality of Indonesian people, which in turn will impact development itself. Therefore, teaching carried out in schools must guarantee students expand their potential so that it will make students able to develop themselves, including thinking skills. The purpose of the research is to know the development of English learning media using Smart Apps Creator (SAC) for 7th-grade junior high school students: the material of introducing oneself and others. The type of research is Research and Development (R&D). In this study, the population of this research was the seventh-grade students of MTS Muhammdiyah Pekanbaru in the 2022 educational period. The sample was taken from a class in the seventh grade, as the research sample was 36 students. Based on the research results and the development of multimedia products for learning English with this communicative approach, English learning multimedia products can effectively be used as a learning medium. This can be seen from the results of students' tests in their understanding of Smart Apps Creator (SAC) on "Introducing Oneself and Others", which shows an increase in learning outcomes from pretest scores to post-test scores or (N-Gain) scores of 0.69 with the category "very good".